KONTRIBUSI GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP MOTIVASI KERJA GURU DI SD NEGERI KECAMATAN SUNGAI PAGU KABUPATEN SOLOK SELATAN - Siska Handayani (Universitas Negeri Padang, 2013)
Based on author observation at SD Negeri Kecamatan Sungai Pagu Kabupaten Solok Selatan showed that there is obstacle with teaching motivated that far from the expectation. It’s because depend on the leadership of head master. The population of this observation is the theacer of SD Negeri Kecamatan Sungai Pagu Kabupaten Solok Selatan as much 83 people. The sample is taking away from technique proportionate sampling rondom stratified equal to 70 people by using Krejcie Table. The analysis of data using simple regression of SPSS 1.5 version. The result of this observation is there is correlation between the contribution of head master leadership to the theacing motivation at SD Negeri Kecamatan Sungai Pagu Kabupaten Solok Selatan, as much 50.7%. Kata Kunci; Gaya Kepemimpinan, Motivasi Kerja Guru